Household polluting cooking fuels and adverse birth outcomes: An updated systematic review and meta-analysis - Luo, Mengrui; Liu, Tiancong; Ma, Changcheng; Fang, Jianwei; Zhao, Zhiying; Wen, Yu; Xia, Yang; Zhao, Yuhong; Ji, Chao (Frontiers in Public Health, 2023)
Background and aim The current study aimed to clarify the association between household polluting cooking fuels and adverse birth outcomes using previously published articles. Methods In this systematic review and meta-analysis, a systematic literature search in PubMed, Embase, Web of Science, and Scopus databases were undertaken for relevant studies that had been published from inception to 16 January 2023. We calculated the overall odds ratio (OR) and 95% confidence interval (CI) for adverse birth outcomes [low birth weight (LBW), small for gestational age (SGA), stillbirth, and preterm birth (PTB)] associated with polluting cooking fuels (biomass, coal, and kerosene). Subgroup analysis and meta-regression were also conducted. Results We included 16 cross-sectional, five case–control, and 11 cohort studies in the review. Polluting cooking fuels were found to be associated with LBW (OR: 1.37, 95% CI: 1.24, 1.52), SGA (OR: 1.48, 95% CI: 1.13, 1.94), stillbirth (OR: 1.38, 95% CI: 1.23, 1.55), and PTB (OR: 1.27, 95% CI: 1.19, 1.36). The results of most of the subgroup analyses were consistent with the main results. In the meta-regression of LBW, study design (cohort study: P < 0.01; cross-sectional study: P < 0.01) and sample size (≥ 1000: P < 0.01) were the covariates associated with heterogeneity. Cooking fuel types (mixed fuel: P < 0.05) were the potentially heterogeneous source in the SGA analysis. Conclusion The use of household polluting cooking fuels could be associated with LBW, SGA, stillbirth, and PTB. The limited literature, observational study design, exposure and outcome assessment, and residual confounding suggest that further strong epidemiological evidence with improved and standardized data was required to assess health risks from particular fuels and technologies utilized.